2005
DOI: 10.1007/s00122-005-1927-6
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and genetic mapping of tuber eye depth in cultivated diploid potatoes

Abstract: Tuber eye depth of the potato (Solanum tuberosum L.) is an important trait for the processing quality and appearance of potatoes. In the present study, we used a cultivated diploid potato family (12601) of 107 plants to dissect the mode of inheritance and to map the gene(s) controlling the trait. The family segregated for both eye depth (deep vs shallow) and tuber shape (round vs long) traits. The deep eye (Eyd) phenotype was found to be associated with round tubers (Ro) in most progeny clones. Further evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 19 publications
2
54
0
2
Order By: Relevance
“…In contrast, overall nucleotide diversity was reduced on chromosome 10. Some of the most conserved genes in the dataset are located near the position of the skin colour, tuber shape and eye depth QTL on chromosome 10 [65][67]. An eye-catching difference between commercial western germplasm and Latin American land races are the highly variable tuber shapes and anthocyanin pigmentation patterns in tuber skin and flesh.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, overall nucleotide diversity was reduced on chromosome 10. Some of the most conserved genes in the dataset are located near the position of the skin colour, tuber shape and eye depth QTL on chromosome 10 [65][67]. An eye-catching difference between commercial western germplasm and Latin American land races are the highly variable tuber shapes and anthocyanin pigmentation patterns in tuber skin and flesh.…”
Section: Discussionmentioning
confidence: 99%
“…Potato diploid clone 11379-03 (DC) (essentially a S. tuberosum L.) [32] was used in this study. DC was derived from a number of crosses between different subspecies of the S. tuberosum group ( S. stenotomum , S. phureja , and S. tuberosum ssp.…”
Section: Methodsmentioning
confidence: 99%
“…Only one study was found in the literature that suggested that eye depth could be efficiently selected in two vastly different environments (Johansen et al, 1965); but details were lacking in the abstract, and the full report was never published. Several studies have shown that deep eye depth is dominant to shallow (Li et al, 2005;Mosquera et al, 2009). The correlations involving tuber eye depth among the locations were low to moderate, ranging from 0.12 to 0.30.…”
Section: Ratingmentioning
confidence: 99%